Um olhar sobre as escolas localizadas no campo do município de Humaitá (Sul do Amazonas): em busca da justiça curricular - Franco, Zilda Gláucia Elias (2018)
This thesis, entitled A look at schools located in the Municipality of Humaitá (Southern Amazonas): in search of curricular justice, sought to build collective understandings about curricular practice in dialogue with teachers and managers of schools located in the field and with the managers of the network of the Municipality of Humaitá - Souther Amazonas, in the light of the concept of curricular justice. The study, linked to the Research Line Public Policies and Educational Reforms of the Postgraduate Program in Education: Curriculum of PUC/SP, was elaborated in the context of the research of the Group of Education and Research in Curricular Justice (GEPEJUC) of CNPq-PUC / SP and adopted as theoretical framework the proposal of Field Education from the concepts of Caldart (1997, 2008, 2009), Caldart et al. (2012), Souza (2012, 2016a, 2016b), Freire (1977, 1983, 2001, 2002), Arroyo (1982, 1999a, 2006, 2011, 2012), and curricular justice through the contributions of curriculum scholars (APPLE, 1989, 2017; TORRES SANTOMÉ, 2013; GIMENO SACRISTÁN, 2000; ARROYO, 1999b, 2007, 2011, 2012; PONCE, 2006, 2016, 2018; CONNELL, 1995; ESTÊVÃO, 2002, 2004), which grounded the dialogue with the material collected in the field research. We chose the methodology of participatory investigation in its articulation with education from Thiollent (2011), Chizzotti (2013), Diniz-Pereira and Zeichner (2011), Brandão and Streck (2006) and Brandão (1999). The methodological proposal materialized with the collaboration of the team of the Municipal Education Secretariat of Humaitá-AM, with 186 educators of the Field Education distributed among 58 schools, parents and students. We analyzed documents, semi-structured interviews, action-reflection scheduled moments with educators, and visits to the communities were carried out. We sought to make sensitive listening of the voices of the subjects that constituted the field of research in order to understand the reality. The study identified that the model of education practiced in schools is rural, it offers a curriculum that aims to ‘transport’ the urban context to the field schools, starting with the school calendar to the pedagogical model, which does not know, in its action and proposition, the characteristics and the needs of the communities, as well as of their subjects. In the context of this research, it was possible to understand that the construction of curricular justice is procedural, it is a daily confrontation of contradictions and presupposes the rise of awareness in the educational process. In the case of Humaitá (AM), it can be based on the affirmation of the conception and practice of Field Education, understanding that curricular justice is moving towards overcoming inequalities and respect for diversity. The knowledge produced from the practice of this participatory research aims to contribute to the education of the people from Humaita, in order to value their way of life, their knowledge and their cultural value in the construction of their identity